1995
DOI: 10.1039/c39950001027
|View full text |Cite
|
Sign up to set email alerts
|

The face-centred ? complex isomer of the benzenium ion is probably the most stable form in the gas phase: experimental evidence

Abstract: Two stable isomers of the benzenium ion are identified by CID MS, the most stable of which appears to be the face-centred TC complex.Arenium ions are important intermediates in electrophilic substitution reactions and have long been of great interest.' The benzenium ion, C6H7+, is the simplest of this class. Although difficult to make in solution Olah et aE.1,2 showed this species to be the CJ complex I1 using NMR spectroscopy. The benzonium form I11 is inferred to be present as the transition state for intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…[33][34][35], MS [36], and theoretical calculations [31,33,34,37] have indicated a planar (C 2v ) complex structure in which the extra hydrogen (to the benzene structure) is -bonded to a carbon. While there is a consensus on the complex being the most stable structure, Mason et al [38] and Dewar [39] have proposed a complex between hydrogen and the system of the benzene ring. In the latter, it is argued that any other structure would not be aromatic and would suffer a significant decrease in resonance energy.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35], MS [36], and theoretical calculations [31,33,34,37] have indicated a planar (C 2v ) complex structure in which the extra hydrogen (to the benzene structure) is -bonded to a carbon. While there is a consensus on the complex being the most stable structure, Mason et al [38] and Dewar [39] have proposed a complex between hydrogen and the system of the benzene ring. In the latter, it is argued that any other structure would not be aromatic and would suffer a significant decrease in resonance energy.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12] Quantumchemical computations also support this assignment and predict that the bridged π -complex (2) is a transition state for a 1,2-H shift within (1) and that the face-centered π complex (3) is a second-order saddle point. 13,14 Early low resolution UV (Refs. 15 and 16) and infrared (IR) (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, Reed et al 11 reported the crystallization of 1 with carboranes as counterions; they analyzed properties such as its thermal stability, NMR spectra, X-ray structure and carried out theoretical calculations for comparison with structural data. Information on the dehydrogenation process of 1 was obtained by Mason et al 12 from collision-induced decomposition experiments. These authors discussed the stability of this cation and suggested that the p complex, the one in which the H atom lies on top of the aromatic ring, has a relevant role in the mechanism as the stable intermediate.…”
Section: Introductionmentioning
confidence: 99%